Lymphoid blast crisis after prolonged treatment‐free remission in chronic myeloid leukaemia after tyrosine kinase inhibitor de‐escalation during the COVID‐19 pandemic - Daniele Avenoso; Dragana Milojkovic; James Clark; Christopher Pocock; Victoria Potter; Deborah Yallop; Guy Hannah (eJHaem, 2022)
Abstract During the COVID‐19 pandemic, access to health services has been considerably restricted and furthermore, patients have been reluctant to attend for routine monitoring, and this may have had a negative impact in the management of patients affected with haematological disorders. Sudden blast crisis in chronic myeloid leukaemia is categorized as a rapid onset of blastic phase, after a documented ‘optimal’ response to tyrosine kinase inhibitor (TKI) therapy and within 3 months of a normal complete blood count. Herein, we describe a case of patient who developed sudden blast crisis after TKI while in treatment‐free remission.